PERBAIKAN ASPEK MANAJEMEN, PRODUKSI DAN HUKUM PADA BUMDES “MAJA UTAMA” DESA TEGAL MAJA KECAMATAN KRAGILAN KABUPATEN SERANG - Fatari, Fatari; Mukhlis, Ahmad; Hifni, Mohammad (Jurnal Abdimas Bina Bangsa, 2025)
The objectives of this Community Partnership Empowerment (PKM) activity are (1) To provide legal assistance related to the legal legality of BUMDes in the form of a Notarial Deed and to increase legal understanding, (2) To increase the knowledge and skills of partners in good and correct business and production management. through the application of science and technology, and (3) To increase the role of BUMDes in empowering the community's economy, so that community welfare also increases. To achieve this goal, the service team prepared an activity plan which included 4 (four) stages, namely stage 1 analysis of the situation and conditions of partners, stage 2 preparation and transfer of science and technology, stage 3 training and mentoring and stage 4 evaluation and program sustainability. By using a chronological method, the implementation of this activity can result in increased knowledge and understanding of law, increased knowledge and skills of partners regarding the management and production of BUMDes. This PKM partner is the Tegal Maja Village Government and the manager of the BUMDes "Maja Utama" Tegal Maja Village.